Brain regions that show repetition suppression and enhancement: A meta‐analysis of 137 neuroimaging experiments. Issue 4 (23rd December 2016) - Kim, Hongkeun
Abstract: Repetition suppression and enhancement refer to the reduction and increase in the neural responses for repeated rather than novel stimuli, respectively. This study provides a meta‐analysis of the effects of repetition suppression and enhancement, restricting the data used to that involving fMRI/PET, visual stimulus presentation, and healthy participants. The major findings were as follows. First, the global topography of the repetition suppression effects was strikingly similar to that of the "subsequent memory" effects, indicating that the mechanism for repetition suppression is the reduced engagement of an encoding system. The lateral frontal cortex effects involved the frontoparietal control network regions anteriorly and the dorsal attention network regions posteriorly. The left fusiform cortex effects predominantly involved the dorsal attention network regions, whereas the right fusiform cortex effects mainly involved the visual network regions. Second, the category‐specific meta‐analyses and their comparisons indicated that most parts of the alleged category‐specific regions showed repetition suppression for more than one stimulus category. In this regard, these regions may not be "dedicated cortical modules, " but are more likely parts of multiple overlapping large‐scale maps of simple features. Finally, the global topography of the repetition enhancement effects was similar to that of the "retrieval success" effects, suggesting that the mechanism for repetition enhancement is voluntary or involuntary explicit retrieval during an implicit memory task. Taken together, these results clarify the network affiliations of the regions showing reliable repetition suppression and enhancement effects and contribute to the theoretical interpretations of the local and global topography of these two effects. Hum Brain Mapp 38:1894–1913, 2017 . ©2017 Wiley Periodicals, Inc.